Assessing the establishment risk for parthenogenetic populations of Lissorhoptrus oryzophilus in global rice-growing areas and potential economic impact in China - Li, Luoyuan; Jin, Zhenan; Li, Ming; Xue, Yantao; Guo, Jianyang; Jia, Dong; Ma, Ruiyan; Lü, Zhichuang; Xian, Xiaoqing; Liu, Wanxue (Frontiers in Plant Science, 2025)
The rice water weevil, Lissorhoptrus oryzophilus Kuschel (Coleoptera: Curculionidae), threatens global rice production, with invasion events driven by its parthenogenetic populations. However, the global establishment risk in global rice-growing areas and potential economic losses and control benefits of the populations in invaded areas remain unclear. We applied an optimized MaxEnt model to predict the global suitable areas of the populations under current and future climate scenarios. Furthermore, we used @Risk software to estimate the potential economic losses and controlling benefit of this populations to rice production in China. Compared to its native range (North America), this populations has explored novel climates ecological niches in invaded areas (Europe and Asia) and occupies the broadest range of climatic ecological niches in Asia. The highly suitable area is primarily covered in rice-growing areas in China, the Korean Peninsula, and Japan, with all major rice-growing areas concentrated in these countries and regions. Under SSP1-2.6 and SSP5-8.5 emission scenarios, sum of suitable area for the populations in global rice-growing regions is projected to decrease by 0.35% and 0.26%, respectively, by the 2030s and 2050s. Moreover, @Risk analysis indicates that without control measures, the populations could cost China’s rice industry $18.95 billion, but management efforts could recover $17.54 billion. These results provide in-depth reference about the impact of climatic changes on the potential global suitable range of L. oryzophilus parthenogenetic populations and its economic impact on the rice industry in China.